Ketimpangan Akses Pendidikan di SDN 112/VI Rantau Kermas Kecamatan Jangkat Kabupaten Merangin: Tantangan dan Solusi - misnawati, ledia (Jurnal Pendidikan Vokasi dan Seni, 2026)
Education is one of the main pillars of social and economic development for a nation, serving as a tool to empower individuals and improve the quality of life in society. In Indonesia, despite various efforts by the government to enhance access to education, disparities in educational access remain a significant issue, particularly in remote areas. This article aims to analyze the disparities in educational access at SDN 112/VI Rantau Kermas, Jangkat District, Merangin Regency, focusing on the challenges faced by students and the school.Through a qualitative approach and secondary data analysis, this study identifies several factors contributing to the disparities in educational access, including inadequate infrastructure, limited human resources, economic factors burdening families, difficult distances and accessibility, as well as limitations in information technology. The research also explores the impact of these disparities on student participation in formal education and their implications for the social and economic development of the local community. Additionally this article offers strategic solutions that can be implemented to improve access to and quality of education at SDN 112/VI Rantau Kermas. These solutions include the construction of adequate educational infrastructure, professional training for teachers, provision of economic assistance to underprivileged families, utilization of educational technology, and mentoring programs between schools in urban areas and remote regions. Thus, this article not only provides a comprehensive overview of the challenges faced in the education sector in remote areas but also presents practical recommendations for enhancing educational access for children in Rantau Kermas